Fluid ordering effects and density variations in nanochannel flows: a quasicontinuum theory. (5th August 2013) - Grammenos, Theophanes; Giannakopoulos, Antonios; Barbatis, Gerassimos; Stratis, Ioannis
<x xml:space="preserve">Abstract</x> A quasicontinuum self‐diffusion theory that can capture the fluid ordering effects and density variations predicted by nonequilibrium molecular dynamics in nanochannel flows is presented. The physics of the problem suggests a fourth order diffusion equation for the concentration as a function of position and time requiring the classic diffusion coefficient D and a microstructural internal length g that relates directly to the shape of the molecular potential of the molecular dynamics simulations. Given the appropriate initial and boundary conditions, the aforesaid linear partial differential equation is analytically solved for the one‐dimensional steady state, whereas the case of symmetric as well as asymmetric wall conditions has been accounted for by examining different inhomogeneous diffusion distributions. Copyright © 2013 John Wiley & Sons, Ltd.